(untitled) (mathematica didactica, 2018)
The Wittgenstein language game is used frequently in theoretical mathematical didactic articles as an instrument for the interpretation of meaning-forming processes. In this article, the practicality of the Wittgenstein language game as a means of profitable didactic-relevant reflection in various contexts is demonstrated by means of practical examples. The results of such reflections can be used as a basis for the didactic preparation of mathematical content.